Practical field test on newly designed burial type lowland power cultivator for effective weed control in North-Central province of Sri Lanka - G. V. T. V. Weerasooriya (Tropical Agricultural Research, 2016)
Weed competition causes significant reduction of rice yield in Sri Lanka. Power weeders have been promoted as an alternative measure to face restricted use of some of the weedicides in Sri Lanka. A new burial type lowland power cultivator has been designed; however, has not been field tested yet hence not been considered for recommending to farmers. Therefore, this study was conducted to test the suitability/adaptability of this new cultivator under the field conditions. When tested the cultivator showed satisfactory field performances with 0.03 ha/h effective field capacity, 83.25% field efficiency, 80% weeding efficiency, and 580 performance Index. Despite 6.34% plant damages, 22 maximum number of tillers, 6968 kg/ha paddy yield was recorded. Further the calculated cost for weeding was Rs. 7671/ha under the field test. Further, the calculated fuel consumption, labour and power requirement were 0.503 L/h, 33 man-h/ha and 0.319 kW, respectively. Interestingly, no ergonomic or mechanical defects were reported during the field test. Given above, new burial type lowland power cultivator can be considered for recommending to farmer after conducting further detail ergonomic evaluations via future investigations.